2007
DOI: 10.1111/j.1439-0507.2007.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytoses in outpatients attending the Dermatology Center of Avicenna Hospital in Qazvin, Iran

Abstract: Dermatophytosis is still being considered as one of the major public health problems in many parts of the world. To identify the prevalence and etiological agents of dermatophytoses, a study was carried out between 2004 and 2006. Out of 1023 subjects suspected to have cutaneous mycoses, 348 (34%) patients were affected with dermatophytoses. The causative agents were identified macroscopically and microscopically after the clinical samples were subjected to potassium hydroxide examination and culture isolation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 25 publications
(96 reference statements)
7
52
2
1
Order By: Relevance
“…Our results confirm those of previous studies in Iran [13,24] and other regions of the world [32,33]. However, our finding is in contrast to others who reported tinea pedis [17,18], tinea capitis [15,32], and tinea cruris [19,20] as the predominant clinical observations in north and center of Iran.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our results confirm those of previous studies in Iran [13,24] and other regions of the world [32,33]. However, our finding is in contrast to others who reported tinea pedis [17,18], tinea capitis [15,32], and tinea cruris [19,20] as the predominant clinical observations in north and center of Iran.…”
Section: Discussioncontrasting
confidence: 70%
“…Despite the variability of fungal species by geographic regions in 1990s, zoophilic fungi such as T. verrucosum overwhelmed the anthropophilic across some regions of the country, including certain endemic areas [14][15][16]. However, today anthropophilic T. mentagrophytes (T. interdigitale), Epidermophyton floccosum, and T. rubrum are the main pathogens in Iran [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In another two studies in India in 2015 and 2010, T. rubrum was the commonest dermatophyte isolated, similar to our study [3,10]. However in a study conducted by Agharmirian et al in Iran [11], Epidermophyton floccosum was the commonest dermatophyte isolated, while M. canis was most commonly isolated in the studies conducted by Fortuño et al [12] in Spain and Mangiaterra et al [13] in Argentina. However Weitzman et al [14] commonly isolated T. tonsurans in the United States and Nowicki et al [15] in Poland and Abu-Elteen et al [16] in Jordan observed T. mentagrophytes as their common dermatophyte.…”
Section: Discussionsupporting
confidence: 89%
“…Candida spp (24.9%) was the second prevailing pathogen recovered from our patients with dermatomycoses, a rate correlating well with comparable studies [24,28,30,34,35]. Fingernails were affected than toenails and females were affected more than males, like findings reported by Kiraz [34] and this may probably attributed to frequent emersion of hands in water.…”
Section: Resultssupporting
confidence: 76%